Evidence of a role for fibroblast transient receptor potential canonical 3 Ca2+ channel in renal fibrosis - Saliba, Youakim (2015)
Fil: Saliba, Youakim. Saint Joseph University. Faculty of Medicine. Pole of Technology and Health. Physiology and Pathophysiology Research Laboratory; Libano